Oksidentalisme Terhadap Boikot Produk Amerika Serikat: Gagasan Kiri Islam Hasan - Falahyakti, Qoriatul (ITB AAS INDONESIA Surakarta, 2024)
Hasan Hanafi is a philosopher who developed Islamic Leftist thought. Through this, he initiated Occidentalism. In this era, the attitude of Occidentalism can be carried out by boycotting American products. It cannot be denied that American products have helped drive national economic growth because the Indonesian population and management of natural resources depend on American products. However, this boycott was carried out in order to develop the national market for more consumption by the Indonesian people. Furthermore, on the one hand, boycotting American products may not be effective because economic relations between Indonesia and the US have been legitimized by regional and international trade organizations. On the other hand, Indonesian people's dependence on consuming US products is still relatively high, as evidenced by the large volume of imports and exports in the two countries. The government's economic policy is influenced by cooperation with other countries so that a boycott will not have an impact on reducing consumption of American products. However, this is worth trying in order to develop domestic products